European policies on short sea shipping and their impact on 'private operators'. (1st January 2012) - Paixão Casaca, Ana Cristina
The environmental damages caused by road transport led European Commission to present a series of measures to promote the use of environmentally friendly transport modes or a combination of such modes, where the role and the impact of road transport could be minimised. Short sea shipping was identified as one of the transport modes that offered this potential. Since 1992, the commission embarked on a promotion programme, which was further sustained by the development of the 'trans-European transport networks' and by what was called an 'integrated maritime policy'. This paper analyses the impact of European policies on short sea shipping private operators . The findings suggest that the final and desired development of the short sea shipping industry may be delayed given the numerous issues that the industry needs to meet to fulfil the policies in the area of: transport, maritime, short sea shipping and intermodal given the present European bad economic and financial situation.